2019
DOI: 10.3390/pr7100732
|View full text |Cite
|
Sign up to set email alerts
|

Overall Adaptive Controller Design of PMSG Under Whole Wind Speed Range: A Perturbation Compensation Based Approach

Abstract: This paper proposes an adaptive overall control strategy of the permanent magnet synchronous generator-based wind energy conversion system (WECS) in the whole wind speed range. For the machine side, the maximum power point tracking (MPPT) operation is realized by stator current and mechanical rotation speed control under below-rated wind speeds. Under above-rated wind speeds, the extracted wind power is limited via pitch control. For the grid side, the reactive and active power injected into grid is regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…And when the wind speed fluctuates up and down at the switching point, it cause frequent switching of the control modes, which would cause oscillation of the unit and affect the safety and reliability. The literature [7] proposes an adaptive overall control strategy for a permanent‐magnet synchronous generator (PMSG)‐based wind energy conversion system (WECS) over the entire wind speed range, which achieves the control objective without knowledge of the complete state information and accurate system model. However, this control strategy required the addition of new observers, making the system more complex.…”
Section: Introductionmentioning
confidence: 99%
“…And when the wind speed fluctuates up and down at the switching point, it cause frequent switching of the control modes, which would cause oscillation of the unit and affect the safety and reliability. The literature [7] proposes an adaptive overall control strategy for a permanent‐magnet synchronous generator (PMSG)‐based wind energy conversion system (WECS) over the entire wind speed range, which achieves the control objective without knowledge of the complete state information and accurate system model. However, this control strategy required the addition of new observers, making the system more complex.…”
Section: Introductionmentioning
confidence: 99%
“…A model predictive controller design method is proposed for Maximum Power Point Tracking (MPPT) systems based on the DPMSG [12]. The adaptive overall control in the whole wind speed range increases the robustness of the DPMSG-based WPS [13]. The modeling and control methods of the DPMSG-based WPS are compared and analyzed, and the direction of future research is demonstrated in [14].…”
Section: Introductionmentioning
confidence: 99%
“…This DC voltage control system for the DC-link requires voltage sensors to obtain information about the voltage. Energy storage units, such as condensers and batteries, are used to manage the load when a tension and disturbance emerges [9][10][11]. The use of these energy storage units restricts the unified power quality conditioner's (UPQC's) ability to compensate because energy storage capacities are limited.…”
Section: Introductionmentioning
confidence: 99%